2005
DOI: 10.1526/0036011054831189
|View full text |Cite
|
Sign up to set email alerts
|

Social Guardianship and Social Isolation: An Application and Extension of Lifestyle/Routine Activities Theory to Rural Adolescents*

Abstract: Although the overall crime rate dropped between 1993 and 2000, both adolescent violence and violent crime in rural areas has been on the rise. However, little research has been conducted on the determinants of rural violence using targeted regional samples of rural youth. This study examines the applicability of lifestyle/routine activities (RA) theory to a large sample of rural adolescents from Alabama. Multivariate logistic regression analyses indicate that: (1) social guardianship reduces the risk of assaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
97
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 49 publications
7
97
0
Order By: Relevance
“…It assumes that aggregate level characteristics, such as population stability or the proportion of two-parent families, for example, are indicators of a community's cohesion and common identity. In nonometropolitian areas, criminologists and rural sociologists see a variety of ways that cohesion may be threatened, including rapid population and/or economic growth, growing urbanization, high levels of unemployment and persistent poverty, and a variety of other structural-level social and economic conditions (Arthur 1991;Carcach 2000a;Jobes 1999;Kaylen & Pridemore 2011;Krannich et al 1985;Lee, Maumee & Ousey 2003;Osgood & Chambers 2000;Reisig & Cancino 2004;Rephann 1999;Spano & Nagy 2005;Wells & Weisheit 2004;Wilkinson 1984aWilkinson , 1984bWood 1942). Many scholars of rural life also point to the diffusion of urban culture and values as a basic, long-term shift that influences individual behavior and the integration of individuals and groups in nonmetropolitian localities (Fischer 1980;Wilkinson 1984a).…”
Section: A Macro-level Perspective On Informal Social Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…It assumes that aggregate level characteristics, such as population stability or the proportion of two-parent families, for example, are indicators of a community's cohesion and common identity. In nonometropolitian areas, criminologists and rural sociologists see a variety of ways that cohesion may be threatened, including rapid population and/or economic growth, growing urbanization, high levels of unemployment and persistent poverty, and a variety of other structural-level social and economic conditions (Arthur 1991;Carcach 2000a;Jobes 1999;Kaylen & Pridemore 2011;Krannich et al 1985;Lee, Maumee & Ousey 2003;Osgood & Chambers 2000;Reisig & Cancino 2004;Rephann 1999;Spano & Nagy 2005;Wells & Weisheit 2004;Wilkinson 1984aWilkinson , 1984bWood 1942). Many scholars of rural life also point to the diffusion of urban culture and values as a basic, long-term shift that influences individual behavior and the integration of individuals and groups in nonmetropolitian localities (Fischer 1980;Wilkinson 1984a).…”
Section: A Macro-level Perspective On Informal Social Controlmentioning
confidence: 99%
“…More recently, scholars have applied the tenets of social disorganization theory to rural areas, examining crime rate variations with the social and economic traits of locations with smaller populations (Kaylen & Pridemore 2011;Jobes et al 2004;Reisig & Cancino 2004;Spano & Nagy 2005;Wells & Weisheit 2004;Wilkinson 1984aWilkinson , 1984b.…”
Section: A Macro-level Perspective On Informal Social Controlmentioning
confidence: 99%
“…Hence, since official statistics, such as the FBI's Uniform Crime Reports, show national level urban crime rates higher than rural crime rates, all or almost all rural communities are presumed to be relatively crime free. This myth has been sharply challenged in recent years by those who contend that there are different types of rural communities and important variations between these communities in terms of issues related to crime (Barnett and Mencken 2002;Donnermeyer et al 2006;Jobes et al 2004;Lee et al 2003;Chambers 2000, 2003;Spano and Nagy 2005).…”
Section: Conceptualizing and Decoupling Ruralmentioning
confidence: 99%
“…Recent studies found some elements of the antithesis of collective efficacy-social disorganization-in US rural communities, which are associated with arrest rates for youth violence, homicide, fear of crime and a host of other criminological phenomena (Barnett and Mencken 2002;Krannich et al 1989;Lee et al 2003;Chambers 2000, 2003;Petee and Kowalski 1993;Spano and Nagy 2005). 7 Here, social disorganization is defined as ''the inability of a community structure to realize the common values of its residents and maintain effective controls'' (Sampson and Groves 1989, p. 777).…”
Section: Conceptualizing and Decoupling Ruralmentioning
confidence: 99%
“…The Seydlitz et al (1993) article was the beginning of a steady parade of published studies of rural communities and crime utilizing social disorganisation theory or a closely related variant (Barnett and Mencken 2002;Bouffard and Muftić 2006;Cancino 2005;Ceccato and Dolmen 2011;Deller and Deller 2010; Donnermeyer, Jobes and Barclay 2009;Jobes 1999;Jobes Barclay, Weinand and Donnermeyer 2004;Jobes, Donnermeyer and Barclay 2005;Kaylen 2010;Kaylen and Pridemore 2011Lee 2006Lee , 2008 Bartkowski 2004A, 2004b;Lee, Maume and Ousey 2003;Lee and Ousey 2001;Lee and Thomas 2010;Li 2012;Mencken and Barnett 1999;Osgood and Chambers 2000;Ousey and Lee 2010; Resig and Cancino 2004;Spano and Nagy 2005;Tunnell 2006; Weisheit 2004, 2012). To a great extent, this 2 Portions of this paper are from two sources: (1) …”
mentioning
confidence: 99%